Weak Molecular Interactions in Clathrin-Mediated Endocytosis - Smith, Sarah M.; Baker, Michael; Halebian, Mary; Smith, Corinne J. (Frontiers in Molecular Biosciences, 2017)
Clathrin-mediated endocytosis is a process by which specific, membrane-localised cargo are internalised from the cell periphery for delivery to early endosomes. The key stages in this step-wise process, from the starting point of cargo recognition, to the later stage of assembly of the clathrin coat, are dependent on weak interactions between a large network of proteins. This review discusses the structural and functional data that has improved our knowledge and understanding of the main weak molecular interactions implicated in clathrin-mediated endocytosis, with a particular focus on the two key proteins: AP2 and clathrin.